Fiqih Learning Method According To Hasan Ja'far Kholifah And Kamaluddin Muhammad Hasyim - 'Azizah, Alviatul; Basuki, Basuki (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Fiqh is a science that explains Islamic laws. To be able to convey this knowledge, there is a need for a fiqh learning method so that it can be well received by students. This research aims to describe the method of learning fiqh according to the thoughts of Hasan Ja'far Kholifah and Kamaluddin Muhammad Hasyim in their book entitled "Fushulun Fii Tadriisi at-Tarbiyati al-Islamiyati". To achieve this goal, researchers used a library method using two data sources, namely primary data sources in the form of a book entitled "Fushulun Fii Tadriisi at-Tarbiyati al-Islamiyati", and secondary data sources, namely books and related journals. The results of this research explain that 5 methods are suitable for learning fiqh, including teaching methods, demonstrations, question and answer, reading, and drill. Using appropriate learning methods, students will easily accept the material presented, so that they can achieve the educational goals that have been determined.   Keywords: Methods, Learning, Fiqh